2005
DOI: 10.1055/s-2004-826115
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin als Marker der schweren Sepsis bei einer immunsupprimierten Patientin

Abstract: A 22 year old female was admitted to the emergency department with high fever up to 41,5 degrees C, tachycardia, and arterial hypotension. Clinically, she presented with bilateral pulmonary coarse crackles. Diagnosis on admission was pneumonia with septic shock. Intriguingly, procalcitonin (PCT) was increased early, reaching up to 435 ng/mL, while C-reactive protein levels were only moderately increased, with several days delay. The sepsis was originated from a multi-resistant pseudomonas aeruginosa pneumonia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Further, Linscheid and colleagues [35] were unable to detect production of PTC mRNA in LPS-activated macrophages or in freshly isolated PBMC, yet a transient expression could be induced following monocytes adhesion [36]. Several investigators showed an increased serum PCT in neutropenic patients [37][38][39], as well as immunodeficient patients [40,41], emphasizing an indispensable role for hematopoietic cells in induction of PCT. The fact that leukopenia had no influence on the rise of PCT on admission to day 2 for sepsis patients with immunosuppression may confirm these conclusions [42].…”
Section: Cellsmentioning
confidence: 99%
“…Further, Linscheid and colleagues [35] were unable to detect production of PTC mRNA in LPS-activated macrophages or in freshly isolated PBMC, yet a transient expression could be induced following monocytes adhesion [36]. Several investigators showed an increased serum PCT in neutropenic patients [37][38][39], as well as immunodeficient patients [40,41], emphasizing an indispensable role for hematopoietic cells in induction of PCT. The fact that leukopenia had no influence on the rise of PCT on admission to day 2 for sepsis patients with immunosuppression may confirm these conclusions [42].…”
Section: Cellsmentioning
confidence: 99%